Achieving service excellence through mystery shopping - Norlia Goolamally; Hii, Yah Mee; Muzliati Ahmad Murad (2019)
To stay at the forefront of the education industry, OUM stays motivated and strong with a refreshed and revived #DareToDream motto. Over the past few years, we have realised our goal and made it happened through various reengineering developments either structurally, technologically or physically to remain fit for purpose for the future. However, in this age where there is intense competition in the education industry, to function like before is no longer sufficient and appropriate. Thus, OUM takes a step back and proactively makes an effort to ‘understand and listen to the voice of the students’ through Mystery Shopping. This paper will present the results of the mystery shopper programme conducted at OUM. For this pioneer project, the research team has selected at random OUM students to serve as mystery shoppers since they are familiar with the academic environment and their expectations may be more in line than an outside shopper. The measurement instrument consists of 50 items based on five constructs. The questionnaire was developed based on a six-point Likert scale from Strongly Disagree to Strongly Agree and followed by open-ended questions for shoppers to give comments and suggestions. Data analysis showed that the average mean score for the five categories are in the range of 4.77–5.01. Although results are on the high side for most items, there are some items in each of the five constructs which require attention. Mystery shopping is an accurate and efficient and effective method to gain in-depth knowledge of customers’ satisfaction and it should be part of the university’s strategic activity. (Abstract by authors)